Prognostic factors for breast cancer squamous cell carcinoma and nomogram development for prediction: population-based research - Cheng, Zhiyuan; Han, Tao; Zhang, Xiaotian; Li, Xizhou; Li, Hengyu; Gu, Jia (Translational Cancer Research, 2019)
Background: To investigate the prognostic survival factors of breast squamous cell carcinoma (BSqCC) and develop a comprehensive nomogram for predicting the survival of breast cancer squamous cell carcinoma. Methods: Data were obtained from the Surveillance, Epidemiology, and End Results (SEER) database to identify patients diagnosed with BSqCC from 1973 to 2015. The data was obtained using SEER Stat 8.3.4 software, collated, and analyzed by Excel 2016 software and SPSS (v25.0). Kaplan-Meier curves were used for survival analysis. The variables obtained by univariate analysis were introduced into the Cox proportional hazard model for multivariate analysis. The risk factors affecting the prognosis of BSqCC were obtained. P